Presynaptic influence on the time course of fast excitatory synaptic currents in cultured hippocampal cells - Mennerick, S (J Neurosci, 1995)
Since the lifetime of synaptically released glutamate is thought to be very brief, reflecting diffusion and glutamate uptake, the decay of synaptic currents is thought to represent the average elementary lifetime of a receptor channel bound only once by transmitter molecules. We show here that the decay of evoked non-NMDA synaptic currents can reflect presynaptic factors, in particular, the prolonged action of transmitter at postsynaptic receptors under conditions of enhanced transmitter release. We show that diffusion, high-affinity glutamate uptake, and non-NMDA receptor desensitization are insufficiently rapid to limit the decays of evoked synaptic currents to those of miniature synaptic currents in microcultures of rat hippocampal cells. Our results are consistent with recent studies suggesting that during evoked release, multiple glutamate quanta can interact with overlapping postsynaptic receptor domains.